2010
DOI: 10.1080/00207540903564942
|View full text |Cite
|
Sign up to set email alerts
|

RFID systems implementation: a comprehensive framework and a case study

Abstract: A growing number of organisations around the world are considering the implementation of radio frequency identification (RFID) systems to improve their business and operations processes. In this study, a multi-stage implementation framework is developed and evaluated through a case study. The framework provides practitioners with a better understanding of the various stages of the RFID implementation process, including guidelines and issues with RFID systems implementation that need to be considered. We illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 17 publications
(26 reference statements)
0
31
1
Order By: Relevance
“…A more recent product tracking and identification tool was created to increase operational efficiency in supply chain management by sharing real-time information and allowing total visibility (Ngai, 2010).…”
Section: Radio Frequency Identification (Rfid)mentioning
confidence: 99%
“…A more recent product tracking and identification tool was created to increase operational efficiency in supply chain management by sharing real-time information and allowing total visibility (Ngai, 2010).…”
Section: Radio Frequency Identification (Rfid)mentioning
confidence: 99%
“…It allows the reader to respond quickly when the signals are received. Ngai and colleagues [12] discussed the different areas of implementations of RFID technology, such as warehouse management, asset tracking, retail, and medical care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The RFID middleware filters data from readers to avoid information overloading, ensures data accuracy, and feeds enterprise resource planning (ERPs) systems with data to control and manage their business systems and operations. Therefore, RFID overcomes the shortfalls of individual manual tracking systems in storing, tracking, wirelessly identifying and communicating information without the need for the object to be within the line-of-sight (Lee and Lee, 2010). Compared to bar-coding, RFID offers (i) reading advantages, as no physical or visual contact is necessary for tags and readers to communicate; (ii) identification advantages, as RFID can be applied at the item level to identify each product, thus offering item traceability and supply chain transparency; and (iii) physical advantages, as tags are safer than barcodes and they last longer, typically 10 years, under extreme environmental conditions such as humidity, heat, vibration, shock, and other conditions frequently associated with warehouse and transportation operations.…”
Section: Rfid Technologymentioning
confidence: 99%
“…Specific supply chain operations, such as tracking, shipping, checkout and counting, become more reliable and faster with RFID technology as the technology provides accurate and timely data for managing the information flows, which, in turn, leads to improved material flow and inventory management (Dai and Tseng, 2012). Moreover, RFID systems offer a wealth of supply chain-related data and information that are used for improving the planning and control of supply chain operations (Ngai et al 2010). Sarac et al (2012) conducted a literature review of 142 articles from 1958 to 2009 that examined the impact of RFID technologies on supply chain management and found that RFID addresses three types of supply chain problems: inventory inaccuracy, bullwhip effect and suboptimal replenishment.…”
Section: Advantages Of Rfid In Supply Chain Managementmentioning
confidence: 99%